Ethical leadership in public management: the Petroperu case 2003- 2005 - Navarro Falconí, Julio César (2018)
This article shows that the application of a management model based on ethical leadership in Petroperu allowed to reverse the situation of economic crisis and the bad reputation that faced as a result of bad management and serious media reports that starred the top executives of the most important company from the country. The new management, in the last four months of 2003 recovered in the short term the economic loss situation it received due to a series of measures applied, as a result of a rapid strategic planning process that involved all the collaborators working together. This economic recovery and the new organizational culture based on four values and four principles were decisive for 2004 to reach extraordinary values in its economic and operational indicators, as well as allowing them to recover and position a new image with a good reputation in the citizenship, consolidating as the first company in Peru.